The content of plant pigments in bottom sediments of Batorino Lake and their spectral pigment indices - Zhukava, Hanna A.; Smolskaya, Volha S.; Vishnevetskaya, Ekaterina A.; Karosienė, Jūratė (Experimental Biology and Biotechnology, 2021)
Studies on the Batorino Lake were aimed at assessing the quantitative and qualitative characteristics of the autotrophic component of bottom sediments, as well as searching for their relationships with the data of spectral analysis of the pigment composition. The content of total chlorophyll a (without correction for the presence of phaeopigments) was relatively low – 12.7 ± 10.2 µg/g wet weight of bottom sediments. The content of carotenoids averaged 10.24 ± 4.89 µg/g wet weight of bottom sediments. It has been shown that pigment indices: Е450 /Е480, Е480/Е664, Е430/Е664, Е430/Е412, characterise the structural indicators of bottom sediments and reflect the long-term trends in the development of primary producers in water ecosystems, primarily phytoplankton. During the preliminary analysis, auxiliary pigment indices for controlling the purity of the extract and the clarity of the prescribed spectrum were calculated: Е664/Е720, Е430/Е720, Е530/Е720, Е412/Е720, Е430/Е530, Е664/Е530, Е412/Е664. A close inverse relationship was revealed between Е430/Е664 index and the amount of chlorophyll a at different depths of bottom sediments (r = – 0.7), as well as an average correlation between the Е430/ Е412 index and the proportion of phaeopigments (r = – 0.56).
Keywords: Batorino Lake; bottom sediments; pigment indices; chlorophyll; phaeopigments; carotenoids